Air assist atomization characterization of palm biodiesel through experimental investigation and CFD simulation - Tan E.S.; Anwar M.; Kumaran P.; Indra T.M.; Yoshikawa K. (Taylor and Francis Ltd., 2023)
Alternative fuels; Atomization; Biodiesel; Combustion; Diesel fuels; Drop breakup; Fluid dynamics; Fossil fuels; Fuels; Gas turbines; Internal combustion engines; Spraying; Two phase flow; Atomization characteristics; Computational fluid dynamics simulations; Environmental concerns; Experimental investigations; Sauter mean diameter (SMD); Spray angle; Spray characteristics; Spray pattern; Computational fluid dynamics